"Não temos tempo de temer a morte": uma etnografia da criatividade política de migrantes racializados em São Paulo durante a pandemia de Covid-19 - Branco-Pereira, Alexandre (2024)
The hegemony of the vulnerability perspective in studies produced on migrants is well known. As a result of an ethnographic research carried out between 2020 and 2023, this work is interested in understanding the political responses that racialized migrants articulated in the face of the end of the world represented by the Covid-19 pandemic. I discuss, through the analysis of political mobilizations in health contexts during the pandemic, how the emic categories of universality and equity are tensioned - often taken as semantically close to privilege. Thus, health is a scarce right - the more people access it, the fewer rights there are to be accessed. The notion of universality - of the SUS, but also of human status - engenders a logic of flattening inequalities by suppressing differences, producing irreconcilable worlds. Such phenomena make up what I call forced forgetfulness mechanisms, which allocate uncomfortable political facts to the realm of hallucinations. Thus, what is real is defined by the indexation of power. It is in this context that migrant movements emerge, with the aim of making what is considered hallucinated real, grounding and guaranteeing the registration of their political demands before the State. This is a work of engaged anthropology that seeks to establish horizontal relationships with its interlocutors, acting not only in cold data prospecting, but seeking to build an anti-basement policy with them.